2016
DOI: 10.1039/c6cp03004a
|View full text |Cite
|
Sign up to set email alerts
|

Ball-milled sulfur-doped graphene materials contain metallic impurities originating from ball-milling apparatus: their influence on the catalytic properties

Abstract: Graphene materials have found applications in a wide range of devices over the past decade. In order to meet the demand for graphene materials, various synthesis methods are constantly being improved or invented. Ball-milling of graphite to obtain graphene materials is one of the many versatile methods to easily obtain bulk quantities. In this work, we show that the graphene materials produced by ball-milling are spontaneously contaminated with metallic impurities originating from the grinding bowls and balls.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
19
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(19 citation statements)
references
References 49 publications
0
19
0
Order By: Relevance
“… 17 , 18 As a result, the ball milling equipment erodes and the performance of the material becomes questionable as it often occurs that the effect of the metallic impurities in the carbonaceous materials is treated as part of the performance of the material. 19 , 20 In this context, noble carbons are very promising candidates for effective ball milling. Noble carbons are a new class of carbon-based materials comprising a high resistance upon oxidation.…”
Section: Introductionmentioning
confidence: 99%
“… 17 , 18 As a result, the ball milling equipment erodes and the performance of the material becomes questionable as it often occurs that the effect of the metallic impurities in the carbonaceous materials is treated as part of the performance of the material. 19 , 20 In this context, noble carbons are very promising candidates for effective ball milling. Noble carbons are a new class of carbon-based materials comprising a high resistance upon oxidation.…”
Section: Introductionmentioning
confidence: 99%
“…The mechanism of graphene exfoliation by ball milling has revealed that the utilization of an auxiliary reagent can facilitate delamination of graphite into graphene nanosheets [24]. Thus, in order to improve the exfoliation efficiency, various auxiliary reagents were used to assist ball milling, such as dry ice [27,28], oxalic acid [25], melamine [29,30], cellulose [31], sulfur [32], and aryl diazonium salt [33], etc. Although researchers have made great progress in this field, the ball milling method still faces some problems, such as low production and long production time [34,35].…”
Section: Introductionmentioning
confidence: 99%
“…Some of them are the alteration of graphene surface [25], point defects [26], edge [27], grain boundary [28], doping and commendatory synergistic effects [29][30][31][32][33][34][35]. Among these, substitutional doping is the easier technique as many of the properties such as electronic [36][37][38][39][40][41][42][43][44][45][46][47][48][49], thermal [50], magnetic [39,51], mechanical [36], transport [36,52], and reactivity [53][54][55][56][57][58][59][60][61][62][63][64][65] can easily be modified with doping. These modifications result in the better novelty of graphene-based systems concerning to their applications.…”
Section: Introductionmentioning
confidence: 99%